2019
DOI: 10.1038/s41598-019-52553-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison study between mesoporous silica nanoscale microsphere and active carbon used as the matrix of shape-stabilized phase change material

Abstract: Mesoporous silica nanoscale microsphere (MSNM), with a special morphology, high porosity, large pore volume and specific surface area, was successfully prepared and used as the matrix material of lauric acid (LA) to prepare a favorable shape-stabilized phase change material (LA/MSNM). The porous network structure of MSNM is effective to prevent the leakage and enhance the thermal stability of LA/MSNM. For comparison, shape-stabilized phase change material of LA/AC, which contained commercially purchased active… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…The calculated fusion and freezing enthalpies of PEG were 183 J/g and 164.6 J/g, respectively, and those of PEG/MPC-Cu were 95.98 J/g and 87.65 J/g, respectively. The measured enthalpy of PEG/MPC-Cu was smaller than the theoretical enthalpy, which was due to the physical limitations of van der Waals forces and capillary forces between the PEG and MPC-Cu in the composite of PEG/MPC-Cu 53 . However, the physical constraints of PEG by MPC-Cu can enhance the thermal stability of the PEG/MPC-Cu composite and avoid the leakage of PEG.…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…The calculated fusion and freezing enthalpies of PEG were 183 J/g and 164.6 J/g, respectively, and those of PEG/MPC-Cu were 95.98 J/g and 87.65 J/g, respectively. The measured enthalpy of PEG/MPC-Cu was smaller than the theoretical enthalpy, which was due to the physical limitations of van der Waals forces and capillary forces between the PEG and MPC-Cu in the composite of PEG/MPC-Cu 53 . However, the physical constraints of PEG by MPC-Cu can enhance the thermal stability of the PEG/MPC-Cu composite and avoid the leakage of PEG.…”
mentioning
confidence: 67%
“…However, as the pores of MPC-Cu were filled with air, the thermal conductivity of MPC-Cu decreased, which was only 0.113 W/(m K), and after PEG was adsorbed by MPC-Cu, PEG molecules filled the pores of MPC-Cu. The heat transfer efficiency of PEG is significantly higher than that of air; the heat transfer path occurred through the porous carbon skeletons 53 , which improved the thermal conductivity of PEG/MPC-Cu compared to PEG. Moreover, the thermal conductivity of PEG/MPC-Cu, which was 0.502 W/(m K), improved by 100% and 66.7%, respectively, compared with those of pristine PEG and PEG/MPC.…”
Section: Resultsmentioning
confidence: 99%
“…If too much is added, it will result in large pores. 44 In the end, this research focused on variations in pH, especially the addition of HCl in the synthesis of mesoporous silica. The addition of the right pH conditions will produce mesoporous silica with high porosity and a large surface area.…”
Section: Resultsmentioning
confidence: 99%
“…in a different study also showed that no heat of fusion was detected at 40% wt. loading, indicating the formation of the non-melting layer [ 141 ].…”
Section: Phase Change Materials Containing Porous Silica Matrices mentioning
confidence: 99%